Emotional Reassurance and its relationship with family climate at the students of kindergarten Department (Journal of the College of Education for Women, 2019)
The research aims to identify the level of emotional reassurance and level of family climate atthe students of kindergarten Department.Search tool :The two researchers built a measure of emotional reassurance and consisting of (26) items andthe scale of family climate consisting of (30 ) items .The applied Statistical methods:The two researchers used the statistical bag spss and they used t-test and Pearson correlationcoefficient and analysis of variance and Alpha -Cronbach .The results showed : The students of kindergarten Department have a high level ofemotional reassurance and good family climate and there is a relationship between emotionalreassurance and family climate .The two researchers have got some recommendations and proposals .